Integrasi Media Gambar Berseri dan Model Experiential Learning dalam Meningkatkan Kemampuan Menulis Siswa Kelas V Sekolah Dasar - Nadia Salsabilla; Zainal Abidin; Rahima Nurviani (Alma Ata University Press, 2026)
This study aims to determine the eﬀect of integrating image series media and the Experiential Learning model on the ability to write simple essays of ﬁfth-grade elementary school students. This study used a quantitative method with a quasi-experimental approach with a one-group pretest- posttest design. The subjects were 28 ﬁfth-grade elementary school students. Data collection techniques were carried out through a simple essay writing test given before and after treatment and observation of student activities. The assessment instrument covered aspects of content, organization, vocabulary, language use, and mechanics. Data analysis was carried out through a normality test using the Shapiro-Wilk test and a hypothesis test using a paired sample t-test. The results showed that students' writing ability improved after the implementation of the Experiential Learning model assisted by picture series media. The mean pretest score increased from 62.43 to 73.43 in the posttest, with an improvement of 11 points. The results of the paired sample t-test showed a signiﬁcance value of p < 0.05, indicating a signiﬁcant diﬀerence between the pretest and posttest results. Furthermore, the observation results showed an increase in students' activeness, creativity, and self-conﬁdence during the learning process. Therefore, the integration of picture series media and Experiential Learning model signiﬁcantly aﬀects the improvement of students' simple essay writing skills.